The impact of innate immune cells on immunopathology in dengue - Howells, A (2014)
Dengue virus (DENV) is an arthropod-borne virus and has become a worldwide problem with steadily rising annual infection rates. Patients present with a range of symptoms from mild fever to, in some cases, life-threatening hemorrhagic fever and shock syndrome. The most severe cases require emergency hospital care and currently, there is no effective drug treatment or vaccine for dengue. As severe symptoms appear post-peak viremia, immuno-pathology is thought to be the cause and a potential trigger of this is differential activation of the immune response upon recognition of DENV. This could be due to a combination of factors including varying receptors, signalling pathways and immune regulation mechanisms. In order to understand DENV infection better, it is imperative to study the mechanisms of activation and control of immune responses triggered by the virus. Very early events in viral infection (after 10 min stimulation) were studied aiming to identify proteins involved in differential activation of immune responses. Phosphorylated proteins were isolated from cells post-stimulation and analysed by mass spectrometry. More than 200 proteins were differentially regulated by phosphorylation in response to DENV stimulation as compared to Mock, Influenza A virus and LPS stimulation. The effect of two specific proteins, namely Calpain-2 and Importin-5, identified to be differentially phosphorylated was investigated further. Calpain-2 was seen to be vital in the efficient production of progeny virions and the transcription of Mx1, an anti-viral interferon stimulated gene. Importin-5 is known to transport DENV NS5 into the nucleus during infection and was seen to co-precipitate with many host proteins. In summary, it is imperative that novel treatments and vaccines are developed for dengue as it is one of the world’s most prevalent arthropod-borne viruses. It was discovered here that many proteins undergo phosphorylation/de-phosphorylation in response to DENV stimulation to a differing degree than other stimuli. Calpain-2 plays a vital role DENV infection, potentially influencing the potency of immune response. Importin-5 associates with various host proteins during DENV infection, potentially altering their function or the function of Importin-5 itself. Research into targeted inhibition of Calpain-2 function or Importin-5 interaction with DENV NS5 could lead to a successful anti-viral treatment for DENV infection.